Development of Hydrogenated Microcrystalline Silicon-Germanium Alloys for Improving Long-Wavelength Absorption in Si-Based Thin-Film Solar Cells - Yen-Tang Huang; Hung-Jung Hsu; Shin-Wei Liang; Cheng-Hang Hsu; Chuang-Chuang Tsai (International Journal of Photoenergy)
Hydrogenated microcrystalline silicon-germanium (μc-Si1-xGex:H) alloys were developed for application in Si-based thin-film solar cells. The effects of the germane concentration (RGeH4) and the hydrogen ratio (RH2) on the μc-Si1-xGex:H alloys and the corresponding single-junction thin-film solar cells were studied. The behaviors of Ge incorporation in a-Si1-xGex:H and μc-Si1-xGex:H were also compared. Similar to a-Si1-xGex:H, the preferential Ge incorporation was observed in μc-Si1-xGex:H. Moreover, a higher RH2 significantly promoted Ge incorporation for a-Si1-xGex:H, while the Ge content was not affected by RH2 in μc-Si1-xGex:H growth. Furthermore, to eliminate the crystallization effect, the 0.9 μm thick absorbers with a similar crystalline volume fraction were applied. With the increasing RGeH4, the accompanied increase in Ge content of μc-Si1-xGex:H narrowed the bandgap and markedly enhanced the long-wavelength absorption. However, the bias-dependent EQE measurement revealed that too much Ge incorporation in absorber deteriorated carrier collection and cell performance. With the optimization of RH2 and RGeH4, the single-junction μc-Si1-xGex:H cell achieved an efficiency of 5.48%, corresponding to the crystalline volume fraction of 50.5% and Ge content of 13.2 at.%. Compared to μc-Si:H cell, the external quantum efficiency at 800 nm had a relative increase by 33.1%.